A 2019 Nexus Social Accounting Matrix for Egypt - Serag, Eman; Ibrahim, Fatma; El Araby, Zainab; Abd El Latif, Mona; El Sarawy, Mahmoud; El Zaabalawy, Dalia; El Dib, Saad Allah; Salem, Kotb; Breisinger, Clemens; Raouf, Mariam (International Food Policy Research Institute, 2021)
The Central Agency for Public Mobilization and Statistics (CAPMAS) is pleased to present an updated social accounting matrix (SAM) for Egypt. This SAM combines information from national datasets from many institutions, including the Central Bank, the Ministries of Finance and Agriculture, and various statistical bureaus. It also makes extensive use of data from the Economic Survey and Household Income and Expenditure Survey (HIECS), which is produced by CAPMAS. With this data it becomes possible to provide a detailed update of the socioeconomic status of Egypt. The SAM also allows for more timely analysis of developmental issues and a better understanding the potential economic impacts of changes. The SAM is the main dataset used for economywide modelling of scenarios and simulations. Such modeling has proven to be a powerful evidence-based analytical tool for informing making and for assessing the impact of different interventions, especially during the COVID-19 crisis.